Measurement of Plasma Digoxin Concentration by Radioimmunoassay - Evered, D. C. (1970)
A rapid, sensitive, and precise method for measuring the plasma digoxin concentration has been developed with the radioimmunoassay technique. Seventy patients receiving digoxin were shown to have plasma digoxin concentrations between 0·4 and 5 ng./ml. Preliminary studies show that though there is a positive correlation between total daily dose and the plasma digoxin concentration, the relationship is not close, and a relatively wide range of plasma digoxin concentrations appear to be consistent with effective digitalization.